Development of Citronella Feedmill Online Store - Aziz, Nor Fatin Nabila; Mohamed, Rozlini (Applied Information Technology And Computer Science, 2023)
Citronella is currently the sole animal feed and other products store in Durian Tunggal, Melaka. Citronella Feedmill Online Store is a web-based system that aims to systematically handle the ordering and purchase processes for customers as well as the recoding process for administrators. The system is built using an object-oriented approach. Functional and user acceptance testing will be used to evaluate the system. The registration module, product module, order module, payment module, order status module and report module are the system function modules. The web-based was created using a prototyping technique, in which the study was conducted using standard procedures such as initial requirements, design, prototyping, customer assessment, review and updating, and development. At the completion of the project, it is demonstrated that all functionalities are well-run, and majority of respondents are completely satisfied with the overall performance of the built system. The system might be improved in terms of data security and useful features, such as order confirmation through email for future work.